American Militarism 1970 : a dialogue on the distortion of our national priorities and the need to reassert control over the defense establishment. - Knoll, Erwin (The Viking Press, 1969)
Obra de teatro que ilustra la situación conflictiva en El Salvador en la década de los setenta.